Imperialist Feminism and Islamic Law - Salaymeh, Lena 1944- (2019)
This article presents three arguments about defects in imperialist feminism. First, I show that imperialist feminists engage in decontextualized comparisons: they consistently compare Western women to the Muslimwoman, without comparing Muslim men and women or comparing non-Muslim men and women. These inconsistent comparisons are the source of significant misrepresentations of Muslim women. Second, I propose that imperialist feminists view Muslim women through the heteronormative male gaze. That is, when imperialist feminists assess Muslim women's practices, they implement the normative assumptions of heterosexual males in the West. Third, I argue that imperialist feminists incorrectly presume that Western women enjoy full autonomy or fail to recognize that women everywhere do not enjoy full autonomy. I present medieval Islamic legal ideas about a wife's right to sexual fulfillment as evidence that the liberal myth of autonomy is not translatable to orthodox Islamic jurisprudence.
Keywords: Islamic Law; chirurgie esthétique; chirurgie génitale; Choice; choix; Circoncision; Circumcision; Clothing; cosmetic surgery; dominance; genital surgery; imperialist feminism; le féminisme impérialiste; Liberal; libéral; loi islamique; modest; modeste; Sexuality; Sexualité; vêtements